IMPLEMENTASI AJARAN KASIH DALAM MEWUJUDKAN SILA PERSATUAN INDONESIA DI TENGAH-TENGAH KEMAJEMUKAN - Efesus Suratman; Sadrakh Sugiono (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2023)
Indonesia is a country of diverse ethnicities, races, cultures and religions. Diversity often triggers conflicts, one of which is religion. The number of religious conflicts shows the discrepancy between the teachings of love and the facts that exist. Inter-religious conflicts require the realisation of the Precepts of Indonesian Unity with the foundation of love. The realisation of the precepts of Indonesian Unity is related to the precepts. It is a concrete manifestation of the teachings of love that religions teach so that conflict can be prevented and not repeated. The research method used is a descriptive qualitative method, and the approach used is a literature study describing the teachings of love and the precepts of Indonesian Unity. The purpose of this research is so that conflicts in the name of religion that are very detrimental to the Unity of Indonesia can be resolved and can be a preventive measure before the conflict occurs. The findings in the research are that the realisation of the precepts of Indonesian Unity is related to the precepts and is a concrete manifestation of the teachings of love that religions teach so that conflict can be prevented and not repeated. The Indonesian people can realise the spirit and values of Unity and integrity of the founders of this nation.